Effects of postpartum PTSD on maternal mental health and child socioemotional development - a two-year follow-up study - Anna Suarez; Vera Yakupova (BMC, 2024)
Abstract Background Postpartum posttraumatic stress disorder (PP-PTSD) is a prevalent, yet often unrecognized mental health problem, particularly in low- and middle-income countries. Moreover, the long-term effects of PP-PTSD symptoms on maternal well-being and child socioemotional development beyond the first year postpartum remain largely unknown. This study focused on the association between PP-PTSD symptoms within one year after childbirth and maternal depressive symptoms and child behavioral problems two years later. Methods Russian women (n = 419) completed the City Birth Trauma Scale and the Edinburgh Postnatal Depression Scale evaluating symptoms of PP-PTSD and postpartum depression (PPD) via a web-based survey. Mothers also filled in the Beck Depression Inventory that assessed their depressive symptoms and the Child Behavior Checklist that assessed child's behavioral problems 2.24 years later. Results The regression analysis showed a significant association between PP-PTSD and elevated depressive symptoms 2 years later even after adjustment for PPD (β = 0.19, 95% Confidence Interval 0.11, 0.26, p < 0.01). Children of mothers with higher PP-PTSD symptoms had higher internalizing, externalizing, and total behavioral problems, independent of PPD and concurrent depressive symptoms (β > 0.12, p < 0.01 for all). Conclusions Childbirth-related PTSD presents risk for maternal psychological well-being and child socioemotional development beyond comorbidity with maternal depression. Raising awareness about PP-PTSD among families, communities, healthcare providers, and policymakers is essential in order to decrease stigma of childbirth-related distress, particularly, in low- and middle-income countries like Russia, improve support system during the postpartum period, promote mother-infant bonding in affected women, and, thus, prevent long-term consequences of traumatic childbirth for maternal and child mental health outcomes. Clinical trial number Not applicable.